2004
DOI: 10.1073/pnas.0308649100
|View full text |Cite
|
Sign up to set email alerts
|

Mapping a locus for susceptibility to HIV-1-associated nephropathy to mouse chromosome 3

Abstract: HIV-1-associated nephropathy (HIVAN) is a major complication of HIV-1 infection with distinct pathologic features. Introduction of the HIV-1 genome into mice results in a renal disease with all of the histologic and clinical hallmarks of HIVAN on the FVB͞N genetic background (TgFVB). We assessed the influence of genetic background on the development or progression of HIVAN by making F1 hybrids of TgFVB with five other inbred strains (CBA, DBA͞2, CAST͞Ei, C3H͞He, BALB͞c) and determining phenotypes relevant to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
91
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 47 publications
1
91
0
Order By: Relevance
“…One possible explanation is that these transgenic mice are on the C57/b6 background, which is known to be resistant to GS. 23 In contrast, recent studies have shown that podocyte-specific expression of Nef in transgenic mice on the FVB/N genetic background develop significant GS. 24 In these mice, podocytes exhibit a loss of differentiation markers in the absence of proliferation.…”
mentioning
confidence: 86%
“…One possible explanation is that these transgenic mice are on the C57/b6 background, which is known to be resistant to GS. 23 In contrast, recent studies have shown that podocyte-specific expression of Nef in transgenic mice on the FVB/N genetic background develop significant GS. 24 In these mice, podocytes exhibit a loss of differentiation markers in the absence of proliferation.…”
mentioning
confidence: 86%
“…For assessment of the influence of genetic background on the development of HIVAN, Tg26 mice were outcrossed with five other inbred strains to generate F1 hybrids. Transgenic F1 hybrids, which share 50% of their genome from each parental strain, demonstrated striking variations in renal disease, which were independent of transgene expression levels (79). Two strains, CAST/EiJ and Balb/cJ, were completely protected from renal disease.…”
Section: Genetic Susceptibility and Hivanmentioning
confidence: 99%
“…These genetic modifiers may be identified by intercrossing that is susceptible to resistant strains. Therefore, in an informative mapping cohort between the susceptible Tg26 (FVBN/J) and resistant CAST/EiJ strains, a genome-wide analysis of linkage has identified a locus on mouse chromosome 3A1-3 that influences the HIVAN phenotype (named HIVAN1 locus) (79). It is interesting that this locus is syntenic to human chromosome 3q25-27, an interval that shows suggestive evidence of linkage to human diabetic and hypertensive nephropathies (81)(82)(83)(84).…”
Section: Genetic Susceptibility and Hivanmentioning
confidence: 99%
“…Among all animal models, the HIV-transgenic mouse model, which expresses HIV genes on their murine genetic background ("transgenic 26" or "Tg26"), is the most studied one. Based on the existence of different renal phenotypes depending on the mice's genetic background, "HIVAN1" and "HIVAN2", the two susceptibility loci associated with HIVAN in Tg26 mice were identified (Gharavi et al, 2004;Chan et al, 2009).…”
Section: Host Genetic Susceptibilitymentioning
confidence: 99%